2015
DOI: 10.5505/tjoncol.2015.1195
|View full text |Cite
|
Sign up to set email alerts
|

Review of oncology nursing research that conducted by nurses in Turkey and published between 2009-2013: a systematic review

Abstract: RESULTSIn 66% of studies were descriptive. In 38% of the studies, all cancer types were included in the sample. Sample of 94% the of studies were adults, and 31% of the studies were related to "Symptom and Symptom Management" and 65% of this studies were conducted by academician nurses. CONCLUSIONIt was seen that there were a large number of researches conducted in the field of oncology. However it was seen that the majority of these researches have low evidence level, performed by academic nurses, and its sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…International Agency for Research on Cancer (GLOBOCAN) data show that 14.1 cancer cases have developed worldwide, and there have been 8.2 million cancer‐related deaths (Carter, ). World cancer report and Ministry of Health data indicate that cancer‐related deaths in Turkey are ranked second among all causes of death (Bağçivan et al, ; Coleman, ; Stewart & Wild, ; Turkish Statistical Institute, ).…”
Section: Introductionmentioning
confidence: 99%
“…International Agency for Research on Cancer (GLOBOCAN) data show that 14.1 cancer cases have developed worldwide, and there have been 8.2 million cancer‐related deaths (Carter, ). World cancer report and Ministry of Health data indicate that cancer‐related deaths in Turkey are ranked second among all causes of death (Bağçivan et al, ; Coleman, ; Stewart & Wild, ; Turkish Statistical Institute, ).…”
Section: Introductionmentioning
confidence: 99%
“…They have to carry out their professional practices to this end in accordance with the laws and regulations and their own value systems, professional ethical norms, and codes. 6,7 In Turkey, Code of Ethics specified by International Council of Nurses (ICN) is accepted without any change. Previous studies showed that cultural values can influence individuals’ beliefs, ethical decisions, and professionalism.…”
Section: Introductionmentioning
confidence: 99%
“…While evidence-based research is so important for professional nursing, nurses working in the clinic are more limited in this regard. Research conducted in the field of nursing is increasing in Turkey, but these studies are mostly conducted and published by academician nurses (6). In addition to academic nurses, nurses working in the clinic should be a part of the scientific research process concerning improving nursing care quality (7).…”
Section: Introductionmentioning
confidence: 99%